Synthesis and Characterization of Chitosan Linked by Methylene Bridge and Schiff Base of 4,4-Diaminodiphenyl Ether-Vanillin - Ahmad Fatoni; Poedji Loekitowati Hariani; Hermansyah Hermansyah; Aldes Lesbani (Indonesian Journal of Chemistry, 2018)
The synthesis chitosan-methylene bridge-Schiff base of 4,4-diaminodiphenyl ether-vanillin using casting method has been done. The aims of this research were modification chitosan with Schiff base of 4,4-diaminodiphenyl ether-vanillin, formaldehyde and its characterization using FTIR spectroscopy, SEM analysis, 1H-NMR and X-Ray Diffraction analysis. The first step was a synthesis of modified chitosan between chitosan and Schiff base of 4,4-diaminodiphenyl ether-vanillin. The second step was chitosan modified Schiff base of 4,4-diaminodiphenyl ether-vanillin then reacted with formaldehyde through casting method. The result showed that chitosan can be modified with Schiff base of 4,4-diaminodiphenyl ether-vanillin and formaldehyde and this modified chitosan can be linked by methylene bridge (-NH-CH2-NH-) and had azomethine group (-C=N-). The functional group of –C=N in modified chitosan before and after adding formaldehyde appeared at a constant wavenumber of 1597 cm-1. The functional group C-N in methylene bridge detected at 1388 and 1496 cm-1. The chitosan-Schiff base of 4,4-diaminodiphenyl ether-vanillin and Chitosan-methylene bridge-Schiff base of 4,4-diaminodiphenyl ether-vanillin had index crystalline (%)16.04 and 25.76, respectively. The chemical sift of signal proton azomethine group (-C=N-) in modified chitosan detected at 8.44–8.48 and 9.77 ppm. Proton from methylene bridge in modified chitosan appeared at 4.97–4.99 and 3.75 ppm. Surface morphology chitosan-methylene bridge-Schiff base of 4,4-diaminodiphenylether-vanillin had dense surfaces, mostly uniform and regular in shape.